Quality Control Circles-A Tool to Improve Quality of Technical Education - Desai, Sandeep R. (Journal of Engineering Education Transformations, 2010)
The present paper is written with a view to emphasize importance of Quality Control Circles (QCC) to improve quality of technical education. The material presented is the result of extensive study carried out while working as Quality Circle group leader in the institute. The quality circle concept has been accepted in the institute to make the student a total quality personal. The Quality Control Circles are shown to have potential to transform today’s staid education scenario by inculcating quality awareness amongst the students and teachers. Some of the issues focused during study are, attendance in the class, study habits of students, maximum failures in specific subjects, effective conduct of experiments, placement of students and communication and personality development of students. The J 2 step QC methodology if applied effectively gives feasible solution for such problems to implement them. The QC tools such as Pareto diagrams, Fishbone diagrams, brainstorming, Deming cycle etc. are equally good as they are in industries, only difference is that gain is not measured on monetary basis as it is applicable for industries. The ultimate benefits which one is expected to get through introduction of QCC concepts are growth of institute, resolution of problems, and satisfaction of parents, along with team building, attitudinal change, training and leadership qualities ill students which are the basic objectives of Quality Circle activities. The Quality Circle as a tool for quality assurance and process improvement may also be able to improve faculty identification, help to develop teaching standards and thus decrease dissatisfaction, as the basic goal is to achieve academic excellence.